Effect of Gas Sparging on Fouling and Fouling Mechanism During Microfiltration of Pineapple Juice and Coconut Water - Laorko, A.; Youravong, W.; Tongchitpakdee, S. (Journal of Applied Membrane Science & Technology, 2017)
Flux reduction due to fouling is the major problem during microfiltration. This study aimed to investigate the role of gas sparging, an effective technique for flux enhancement, on fouling and fouling mechanism during microfiltration pineapple juice and coconut water. A hollow fiber membrane was used and the experiments were performed at cross flow velocity (CFV) of 1.5 m/s, transmembrane pressure (TMP) of 0.7 bar for pineapple juice and CFV of 1.6 m/s, TMP of 0.6 bar for coconut water, as varying gas injection factors (e). It was found that the fouling mechanism during microfiltration of pineapple juice and coconut water began with complete blocking, followed by an intermediate blocking and finally cake filtration. The use of gas sparging did not affect the sequence of fouling mechanism but affected both intensity duration of these fouling mechanisms. The duration of complete blocking stage was about 5-6 min at the beginning of the microfiltration for both feed. The initial points of defined cake filtration stages reduced from 1.3 to 0.9 h for pineapple juice and 1.0 to 0.67 h for coconut water when the e was varied from 0 to 0.35. Regarding fouling resistance analysis, increase in gas injection factor could significantly reduce the reversible fouling, external irreversible fouling but internal irreversible fouling.